TFN Brownie / Nur Syazwana Syahirah Bakir - Bakir, Nur Syazwana Syahirah (2021)
TFN Brownie stand for The Famous Nisha Brownie which the most thin and crunchy brownie. This business started their operation on March 2021 that based on Pahang state. It offers four type of flavour including Chocolate Chip, Walnut, Mint and also Red Velvet. The hot seller flavour goes to the Chocolate Chip. The price range is affordable and mostly our customer bought in sale which give them more save. With the attractive packaging, TFN Brownie targeted customer for those who has no idea on choosing their snacks. This especially during their leisure time, but we also give the better way for whom that bored with everyday routine meal. So, this is the best decision for them to make TFN Brownie as breakfast, supper or anytime and everywhere they need. Along with that, our brownie serve and suite to all age’s level but the most recommendation for students and kids. Those customer who ordered with us, we provide cash on delivery (COD) which only for specific area in Temerloh town with delivery charge and postage for whole country. We used J&T Express courier to speed up the delivery process to the customer. The delivery and postage also available every day. Every process on packaging, delivering, marketing are all done by myself. We also keep up to date with our customer to get feedback and this is the one of our strategy to stay engaged with them. This will increasing the number of customer repeat order and keep loyal with our product as their snack. Within that, I have already create my first social media platform which Facebook Page for expanding my TFN Brownie business to other society with various type of promotion. Our Facebook Page named as TFN Brownie Pahang. The posting that I has made to attract my customer started with teaser then followed by soft selling and after that proceed with hard selling post. Our customer can freely contact with us either by direct messages on Facebook, or used Whatsapp link that has already provided in our bio.